Product carbon footprints as tool for a low-carbon economy - Reusswig, Fritz (Ökologisches Wirtschaften - Fachzeitschrift, 2008)
Stabilizing greenhouse gas emissions at a level that prevents a global warming beyond plus two degree celsius is a formidable challenge. The required emission reductions can only be achieved by a series of technological, organizational and social innovations.
Keywords: Greenhouse Gas Emissions; Global Warming; Product Carbon Footprints